A Guide to Christian Freedom and Liberation - Razinger, Joseph Alois (Journal of Research for Christianity in China (JRCC), 2025)
His Holiness Pope John Paul II approved this Directory during an audience with Cardinal Joseph Ratzinger, who signed it. The Ordinary Session of the Congregation for the Doctrine of the Faith adopted it and directed its publication.Issued in Rome, on March 22, 1986, the Solemnity of the Annunciation of the Lord.Joseph Ratzinger, Prefect of the Congregation for the Doctrine of the FaithAlberto Bouvon, Honorary Archbishop of Caesarea in Numidia, Secretary of the Congregation